2022
DOI: 10.3390/cancers14163845
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Treatment of Pheochromocytoma: A Critical Appraisal

Abstract: The management of pheochromocytomas has significantly evolved these last 50 years, especially with the emergence of new technologies such as laparoscopic procedures in the 1990s. A preoperative blockade using antihypertensive medications to prevent intraoperative hemodynamic instability and cardiocirculatory events is recommended by current clinical guidelines. However, these guidelines are still based on former experiences and are subject to discussion in the scientific community. The aim of this systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
6
0
4
Order By: Relevance
“…Nevertheless, there was no difference between SAB and NSAB in terms of time of out-of-target BP during resection, and it could not be established whether its use was associated with a better clinical outcome (including hypotension, vasopressor requirements, cardiovascular complications and mortality). According to recent studies, no difference has been reported between alpha blockade vs. no blockade in terms of mean SBP, HR, cardiovascular morbidity or mortality [36,37], hence the systematic pharmacological preparation has been questioned [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was no difference between SAB and NSAB in terms of time of out-of-target BP during resection, and it could not be established whether its use was associated with a better clinical outcome (including hypotension, vasopressor requirements, cardiovascular complications and mortality). According to recent studies, no difference has been reported between alpha blockade vs. no blockade in terms of mean SBP, HR, cardiovascular morbidity or mortality [36,37], hence the systematic pharmacological preparation has been questioned [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our patient, the significant ketoconazole-induced reduction in cortisol secretion led to satisfactory BP control on antihypertensive drugs. After the biochemical diagnosis of pheochromocytoma, a selective alpha-blocker was added, and after a few days, a beta-blocker was restarted in order to control reflex tachycardia ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pagrindinis šių neuroendokrininių navikų gydymas yra chirurginis naviko šalinimas, atliekant adrenalektomiją, pirmenybę teikiant laparoskopinei chirurginei intervencijai [1][2][3]6]. Siekiant valdyti galimas komplikacijas, pacientai su neuroendokrininiais navikais turi būti detaliai ištirti, įvertinant naviko dydį, lokalizaciją, galimą metastazavimą.…”
Section: įVadasunclassified
“…Tyrimo rezultatai Priešoperacinis paruošimas: diagnostikos ypatumai ir valdymas. PPGL diagnozės nustatymas pradedamas nuo metanefrinų, normetanefrinų kraujo plazmoje ar paros šlapime biocheminių tyrimų [1][2][3]6,7]. Galimas 3-metoksitiramino tyrimo įtraukimas, nustatant dopaminą produkuojančias PPGL [11,12].…”
Section: Feochromocitoma Ir Paraganglioma Anesteziologijoje Periopera...unclassified
See 1 more Smart Citation